PORTRAIT OF COLONIAL BUILDINGS IN MEDAN CITY - Nabil Akbar Soufyan; Akhmad Fariz Al Daffa Hasibuan; Suthan Muzakky; Awabi Rauf; Nurul Aini (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This research will study the heritage of historical buildings in the colonial era in Medan city. Among them are the London Sumatra Building, Bank Indonesia, Post Office, City Hall Building, and Tirtanadi Tower. In obtaining the data needed to conduct research, researchers conducted a historical research method consisting of four steps: (1) Heuristics, which is collecting historical sources that are interconnected with the topic of the research study. At this stage, the author prepares to collect historical sources in the form of documents, archives, books, documentation, interviews, and tracing photos, maps. Photo and map searches can be done for verification. At this stage, the author conducts source criticism to test whether the historical sources are authentic and credible. All historical sources that have been collected will be tested through internal and external criticism. Internal criticism is carried out to find the validity of the source, while external criticism is carried out to determine the extent to which the validity and authenticity of the sources obtained can be accounted for. After these two steps are carried out, all data that has been validated is then grouped based on the topic of study to be researched. 3. Interpretation. At this stage, the author interprets historical sources into a unified understanding or story about the event. (4) Historiography At this stage, the author reconstructs the events of the past with me.